Role Of Healthy Diet In Wound Healing - Ranjan, Priya; Sundari Verma, Deepali (Journal of Neonatal Surgery, 2025)
Good nutritional status is fundamental for effective wound healing, as the process of tissue repair is metabolically demanding and highly dependent on the availability of essential nutrients. Malnutrition adversely affects cellular function, immune response, and collagen synthesis, thereby compromising the body’s ability to heal wounds efficiently and prolonging the various stages of wound healing. Adequate energy intake is crucial, with glucose serving as the primary fuel source for cellular activities such as fibroblast proliferation, angiogenesis, and deposition of new connective tissue. Insufficient energy supply may result in catabolism of body proteins, further impairing tissue regeneration.Dietary fats, particularly essential fatty acids, play an important role in maintaining cell membrane integrity and modulating the inflammatory response necessary for wound repair. An appropriate balance of fatty acids supports normal inflammatory processes while preventing excessive or prolonged inflammation that may delay healing. Protein is one of the most critical nutrients in wound healing, as it provides amino acids required for collagen synthesis, immune cell activity, and formation of granulation tissue. Protein deficiency is strongly associated with delayed wound healing, reduced wound tensile strength, poor collagen deposition, and increased risk of wound dehiscence. In patients with highly exudative wounds, substantial protein loss may occur, sometimes reaching significant levels per day, which further increases the need for a high-protein diet.Micronutrients also play a vital role in wound healing. Vitamin C is essential for collagen maturation and acts as an antioxidant, while vitamin A supports epithelialization and immune function. Zinc is involved in DNA synthesis, cell proliferation, and immune defense, whereas iron is necessary for oxygen transport and cellular metabolism. Vitamin K contributes to blood coagulation during the initial stages of wound healing. Therefore, early nutritional assessment, identification of deficiencies, and timely dietary intervention are essential components of holistic wound management and significantly improve healing outcomes